Government Policy in Illegal Parking Charges at Public Spaces - Triputro, R Widodo; Giawa, Analius; Suharyanto, Suharyanto; Wijaya, Junior Hendri (Journal of Governance and Public Policy, 2023)
The growth of motorized vehicle ownership has outpaced the limited availability of public land and parking spaces. Illegal parking lots and attendants in Yogyakarta worsen this problem. As an illegal parking area, illegal parking attendants do not have the legality to collect fees from the community, so collecting money from parking users is an act of illegal levies. As a result, the rights of parking users as consumers tend to be neglected without any protection from authorized institutions or officials. This phenomenon is increasingly widespread and has been going on for quite a long time, so the impression appears there is an element of omission by state officials. The research method utilized was a qualitative descriptive, interactive approach that involved collecting data through observation, documentation, and interview. The primary data were recruited through an interview, and some informants were determined with the purposive technique, which was informants or source determination based on a certain consideration. Based on the results,  parking management has been managed in such a way on Regional Regulation of Yogyakarta Number 2 of 2019. Regarding parking, the Regional Regulation (Perda) is followed up with the Mayor’s Regulation of Yogyakarta number 2 of 2019. The objectives of the parking regulations are to embody safe and orderly parking service, implement law protection and certainty, and ensure transparency of Locally-Generated Revenue Receipt in the parking area.